2018
DOI: 10.1111/irv.12509
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in serum cytokines and chemokines in response to inactivated influenza vaccination

Abstract: BackgroundThe timing of host cytokine responses to influenza vaccination is poorly understood.ObjectivesWe examined serum cytokine kinetics following inactivated trivalent influenza vaccine (TIV) to better understand potential relationships between markers of inflammation and TIV‐related side effects.Patients/MethodsTwenty healthy adult subjects received TIV. Cytokines/chemokines were assessed in intervals from 3 hours to 14 days. Antibody titers were measured at baseline and Day 14.ResultsSerum cytokine respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…However, the timing of the expected cytokine response to influenza vaccination has not been well described. In a study in adults who received IIV, serum cytokines were measured at various time points, and it appears that some changed rapidly after vaccination [ 30 ]. Talaat et al reported elevated responses in IFN-γ and CXCL10 as early as 3 hours after immunization, with many returning to baseline within 2 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the timing of the expected cytokine response to influenza vaccination has not been well described. In a study in adults who received IIV, serum cytokines were measured at various time points, and it appears that some changed rapidly after vaccination [ 30 ]. Talaat et al reported elevated responses in IFN-γ and CXCL10 as early as 3 hours after immunization, with many returning to baseline within 2 days.…”
Section: Discussionmentioning
confidence: 99%
“…Talaat et al reported elevated responses in IFN-γ and CXCL10 as early as 3 hours after immunization, with many returning to baseline within 2 days. However, IL-8 was found to be lower compared with baseline for up to 2 weeks [ 30 , 31 ]. A study of adults found that IIV was associated with a higher seroresponse rate than LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines act as effectors or modulators in the innate or adaptive immune system after influenza infection or vaccination and play an important role in development and control of the immune response. Measuring a broad range of cytokines following influenza infection or vaccination therefore provides an insight into the influenza pathogenicity or immunogenicity [242]. The multiplex cytokine assay is now widely used to allow simultaneous detection of a number of cytokines from the same sample, which is particularly important in studies of young children where only small…”
Section: Methodological Considerationmentioning
confidence: 99%
“…Systemic IgG was measured by indirect ELISA using the same procedure described above, and HRP-conjugated rabbit anti-piglet IgG (1:5000; Bioss) was used as the secondary antibody. The cellular response was analyzed by detection of IL-4 and IFN-γ cytokines in serum according to other related research [39,40,41]; in this case, commercial pig cytokine double antibody sandwich ELISA kits (Feiya Biological Technology, Yancheng, China) were used.…”
Section: Methodsmentioning
confidence: 99%